Psychotherapeutic treatment and HPA axis regulation in posttraumatic stress disorder: A systematic review and meta-analysis. (December 2018) - Schumacher, Sarah; Niemeyer, Helen; Engel, Sinha; Cwik, Jan Christopher; Knaevelsrud, Christine
Highlights: There is considerable diversity in study and hormone assessment designs. Changes from pre- to post-test in basal cortisol and in the CAR were not significant. The primary studies found significant changes only in subgroups. Consistent use of established hormone parameters (CAR, slope, AUC) is essential. Further guidelines for standardized hormone sampling procedures are needed. Abstract: Posttraumatic stress disorder (PTSD) has been associated with dysregulation of the hypothalamic–pituitary– adrenal (HPA) axis. Research over the past years has investigated potential changes of these alterations in the context of psychotherapy. Yet, no systematic review has been conducted. To summarize the current state of research on psychotherapy and HPA hormones, namely cortisol, dehydroepiandrosterone and its sulfate form (DHEA(S)), we searched for studies investigating predictions or changes in hormones over treatment course within the databases PubMed, Scopus, Medline, PsychINFO, Pilots/ProQuest, and Web of Science, and in the grey literature up to May 2018. Controlled and uncontrolled trials investigating adult samples with a clinical status of PTSD were eligible for inclusion. Twelve studies (428 participants) were included. Study quality was overall sufficient. Hormone assessment designs differed considerably. Treatment efficacy on PTSD symptom reduction was mostly high, but predictions of pre-treatment hormone concentrations on treatment efficacy were largely non-significant. Changes from pre- to post-test in basal cortisol ( g  = −0.07, 95% CI = −0.36; 0.21) and in the cortisol awakening response ( g  = −0.07, 95% CI = −0.48; 0.35) were also non-significant. Future studies require comparable designs and need to be sufficiently powered to be able to detect potential associations with HPA regulation.